Young specialist in children’s arts education system: Factors of professional career development in self and expert assessments - Anna V. Gagulina (Управление культурой)
The young specialist is mysterious, while full of youthful maximalism and confidence in his abilities and knowledge. Often, novice teachers and concertmasters are reproached by older colleagues that their interest in work is purely material, and it would be necessary to work solely for the sake of the idea that "they used to be better and more savvy." Largely due to the fact that the author of the article also faced the problem of settling in the workplace and the relatively recent change of the status of a "young specialist" to the status of a teacher "with experience", this study became a kind of view from a person who directly worked in the art education system. In order not to turn the research into personal outpourings of yesterday's young specialist, the article uses the experience, materials and analysis of the results of panel discussions of the XIII All-Russian Scientific and Practical Conference in the field of children's art education "Children's Art School: TOP format" as a support and methodological basis. Potential. Process. Progress", held in the spring of 2023 in Yekaterinburg. Despite the relatively small amount of research, it examines a number of problems and analyzes possible ways to solve them related to the work of young professionals in the art education system of Yekaterinburg: lack of motivation to work in Children's art Schools; lack of competencies of graduates of creative universities related to gaps in education; the work of the mentoring system in the city; psychological readiness/unavailability of a young specialist to work at a Children's art school. The author of the text is deeply convinced that not only voicing, but even discussing acute angles to the general public, and possibly a clash of opinions between the two sides, as it was on March 24 at the XIII All-Russian Scientific and Practical conference in the field of art education of children "Children's Art School: TOP format. Potential. Process. Progress" is not just relevant for small-town research, but will allow directing the entire system of art education in the direction of harmonious and professionally sustainable cooperation between all participants in the process.